The integrative metabolomic-transcriptomic landscape of glioblastome multiforme - Heiland, Dieter Henrik; Wörner, Jakob; Haaker, Jan Gerrit; Delev, Daniel; Pompe, Nils; Mercas, Bianca; Franco, Pamela; Gäbelein, Annette; Heynckes, Sabrina; Pfeifer, Dietmar; Weber, Stefan; Mader, Irina; et al. (Oncotarget, 2017)
The purpose of this study was to map the landscape of metabolic-transcriptional alterations in glioblastoma multiforme. Omic-datasets were acquired by metabolic profiling (1D-NMR spectroscopy n=33 Patient) and transcriptomic profiling (n=48 Patients). Both datasets were analyzed by integrative network modeling. The computed model concluded in four different metabolic-transcriptomic signatures containing: oligodendrocytic differentiation, cell-cycle functions, immune response and hypoxia. These clusters were found being distinguished by individual metabolism and distinct transcriptional programs. The study highlighted the association between metabolism and hallmarks of oncogenic signaling such as cell-cycle alterations, immune escape mechanism and other cancer pathway alterations. In conclusion, this study showed the strong influence of metabolic alterations in the wide scope of oncogenic transcriptional alterations.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Glioblastoma multiforme; Metabolomics; Network analysis; Transcriptomics; WGCNA